Laryngeal Chondrosarcoma of the Thyroid Cartilage - Selma ERDOĞAN DÜZCÜ; Zeliha COŞGUN; Hesna Müzeyyen ASTARCI (Federation of Turkish Pathology Societies, 2021)
Laryngeal chondrosarcoma is rare and accounts for 0.2% of all larynx malignancies. Although chondrosarcoma is the most common sarcoma seen in the larynx, laryngeal involvement by cartilage tumors is rare. In this article, we aimed to present the differential diagnosis of chondrosarcoma located in the thyroid cartilage, which is a rare site, in a 75-year-old male patient. The patient underwent total laryngectomy by the otolaryngology department. The macroscopy of the laryngectomy material sent to the pathology laboratory revealed a 3x2 cm tumor with a polypoid extension to the lumen from the bottom of the right vocal cord. Although clinical and radiological findings are important in the diagnosis, the definite diagnosis is based on the pathological examination. It is especially important to differentiate the lesion from chondromas.